(untitled) (Ameghiniana, 2013)
A new rich Silurian Tribolite fauna from Argentina is described. The material was Collected in the Lipeón Fm., that outcroping in the Río de los Tonuztes section ( Zapla Hills, Jujuy Province), near the "9 de Octubre" iron mines. new Association consist in 10 new species, with 5 new genera and 1 news subfamily Pericopyginae). The new genera and species described are: Calymene ferrifera Bal. y Bias. n. sp.; Diacalymene subandina Bal. y Bias. n. sp.; Trimerus (T.) flexuosus Ben. y Mar. n. sp.; T. (T.) grandis Ben. y Mar. n. sp.; Australoacaste palpalensi.Ben. y Mar. n. gen. et sp.; Harringtonacaste haningtoni Bal. y Blas. N gen et sp.; Pericopyge transglabelaris Ben. y Mar. n. p.; Dalmanites sudamericanus Ben y Mar n. Sp.; Jujuyops nonoctubrensi Bal. y Bla . n. gen. et. sp.; Zaplaops zapalensis Bal. Y Blas. N. Gen. Et. Sp. Trilobites were distributed in 5 zones, ubicated into the middle ( lights sandstones) (transitiooal) members of the Lipeón Fm. The age of the fauna suggest a continuos deposition from Wenlockian to Lower Devonian